Exploring therapeutic potential of mitophagy modulators using Drosophila models of Parkinson’s disease - Asthana, Jyotsna; Shravage, Bhupendra V. (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common age-associated neurodegenerative disorder characterized by dopaminergic neuronal loss in the substantia nigra, aggregation of α-synuclein (α-syn), and locomotor defects. The majority of PD cases are sporadic, but mutation in genes such as SNCA, PINK1, Parkin, DJ-1, LRKK2, and others have been identified as the main cause of a familial form of PD. Recent advances have been uncovered the underlying mechanisms of PD but the pathogenesis of PD is still unknown due to the lack of effective treatments and, there are currently no therapies available for the treatment of the disease. The pathophysiology and genetics of PD have been strongly associated with mitochondria in disease etiology. Several studies have investigated a complex molecular mechanism governing the identification and clearance of dysfunctional mitochondria from the cell, a mitochondrial quality control mechanism called mitophagy. Reduced mitophagy and mitochondrial impairment are found in both sporadic and familial PD. Pharmacologically modulating mitophagy and accelerating the removal of defective mitochondria are of common interest towards developing a therapy for PD. However, despite the extensive understanding of the mitochondrial quality control pathway and its underlying mechanism, the therapeutic potential of targeting mitophagy modulation and its role in PD remains to be explored. Thus, targeting mitophagy using chemical agents and naturally occurring phytochemicals could be an emerging therapeutic strategy in PD prevention and treatment. We discuss the current research on understanding the role of mitophagy modulators in PD using Drosophila melanogaster as a model. We further explore the contribution of the fly model in the pathophysiology of PD, discuss comprehensive genetic analysis in flies and pharmacological drug screening to develop potential therapeutic molecules for PD.